Partisipasi Masyarakat Dalam Posyandu Di Kecamatan Sidoarjo - Weni Al Azizah; Isna Fitria Agustina (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
This study aims to describe the role of posyandu cadres in mobilizing community participation, in the role of posyandu cadres strongly influencing the participation of the community due to many obstacles that occur in the implementation of posyandu resulted from decreasing the visit of mothers in posyandu program and increase or move the visit of mothers to come To the posyandu. The method used in this research is qualitative method. Data collection techniques used through observation, documentation, and interviews with posyandu midwives, posyandu cadres, and mothers with toddlers in mobilizing community participation in the candlenut village. The result of this research is the inactivity of posyandu cadres located in Kemiri Village made mothers reluctant to come to posyandu because some mothers considered posyandu one eye and mothers rely more on personal physician, and also lack of cadre that make progress of program of posyandu Become obstructed and disorderly. In addition, the facilities provided are less, many mothers who sat idolnya because of limited seating waiting for mothers and toddlers, as for other obstacles that the program is given settled course there is no new program that can increase the visit of mothers to came to posyandu and lack of innovation from posyandu cadres.